Why some advanced economy firms prefer to be taken over by Chinese acquirers - Jan Knoerich (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Recently, bids by Chinese multinational enterprises for leading companies in advanced economies have multiplied, despite numerous concerns being raised about such acquisitions. This Perspective explains the reasons why target firms find Chinese acquirers uniquely appealing, and explores how governments could position themselves in view of competing perspectives about such deals.
Keywords: 330